2017
DOI: 10.1002/2016gc006660
|View full text |Cite
|
Sign up to set email alerts
|

Iron isotopic evolution during fractional crystallization of the uppermost Bushveld Complex layered mafic intrusion

Abstract: We present δ56Fe (56Fe/54Fe relative to standard IRMM‐014) data from whole rock and magnetite of the Upper and Upper Main Zones (UUMZ) of the Bushveld Complex. With it, we assess the role of fractional crystallization in controlling the Fe isotopic evolution of a mafic magma. The UUMZ evolved by fractional crystallization of a dry tholeiitic magma to produce gabbros and diorites with cumulus magnetite and fayalitic olivine. Despite previous experimental work indicating a potential for magnetite crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…This feature is obviously different from that in the Kilauea Iki lava lake in Hawaii and the Red Hill intrusion in Tasmania (Australia), both of which represent the magma differentiation in a closed system and have a negative correlation between δ 56 Fe whole rock and MgO (Sossi et al, ; Teng et al, ; Figure b). However, the nearly uniform δ 56 Fe whole rock of the Panzhihua intrusion is similar to that for the rocks along the ~2.5‐km‐thick Upper and Upper Main Zone of the Bushveld Complex (Bilenker et al, ; Figure b). Such a trend of δ 56 Fe whole rock in the Upper and Upper Main Zone was considered to reflect limited change of the Fe isotopic compositions of a multiply‐saturated magma; that is, the effect of the magnetite crystallization on the δ 56 Fe of the magma may have been minimized by competing crystallization of other Fe‐bearing cumulus phases, in particular, olivine and pyroxene.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This feature is obviously different from that in the Kilauea Iki lava lake in Hawaii and the Red Hill intrusion in Tasmania (Australia), both of which represent the magma differentiation in a closed system and have a negative correlation between δ 56 Fe whole rock and MgO (Sossi et al, ; Teng et al, ; Figure b). However, the nearly uniform δ 56 Fe whole rock of the Panzhihua intrusion is similar to that for the rocks along the ~2.5‐km‐thick Upper and Upper Main Zone of the Bushveld Complex (Bilenker et al, ; Figure b). Such a trend of δ 56 Fe whole rock in the Upper and Upper Main Zone was considered to reflect limited change of the Fe isotopic compositions of a multiply‐saturated magma; that is, the effect of the magnetite crystallization on the δ 56 Fe of the magma may have been minimized by competing crystallization of other Fe‐bearing cumulus phases, in particular, olivine and pyroxene.…”
Section: Discussionsupporting
confidence: 61%
“…The horizontal light blue shaded region represents the average of δ 56 Fe and 2 standard deviation errors (0.10 ± 0.08‰; 2SD, n = 146) of terrestrial basalts from Weyer and Ionov (), Dauphas et al (), and Teng et al (). (b) Variation of δ 56 Fe Whole Rock versus MgO (wt.%) for the samples in this study, as well as the Kilauea Iki lava lake in Hawaii (Teng et al, ), the Red Hill intrusion in Tasmania (Sossi et al, ), and the Upper and Upper Main Zones of the Bushveld Complex (Bilenker et al, ). The dashed lines indicate the change of Fe isotope composition with magma differentiation in closed systems: green line= Kilauea Iki; blue line = Red Hill intrusion.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Isotopic data for magnetite samples in δ 56 Fe vs. δ 18 O space. The dashed orange box denotes the range for magmatic (igneous) Fe and O isotope values as established byTaylor (1967Taylor ( , 1968,Heimann et al (2008),Weis (2013),and Bilenker et al ( , 2017. Stars denote δ 56 Fe vs.…”
mentioning
confidence: 99%
“…Previous Fe isotope studies on other LMI revealed complex Fe isotope systematics in neighbouring minerals within cumulate layered intrusive rocks Liu et al, 2014), yet without any systematic variations, and even in the case of the Bushveld Complex, without notable isotope fractionation (Bilenker et al, 2017). Here, we measured Fe isotope compositions in cumulate rocks with known variable whole-rock Hf isotope systematics that relate to magma mixing, which vary with intrusion depth (Nebel et al, 2013a).…”
Section: Introductionmentioning
confidence: 78%